Differentiated Instruction in Improving Indonesian Language Learning Outcomes Based on Visual, Auditory, and Kinesthetic Learning Styles - Nur Asmi; Ulfah Rizki Afdilah; Aliem Bahri (Universitas Pendidikan Mandalika, 2026)
Education plays a strategic role in developing students’ potential; however, low learning outcomes remain a persistent challenge, often resulting from teaching methods that fail to accommodate diverse learning styles. Recognizing that learners possess distinct preferences—visual, auditory, or kinesthetic—this study emphasizes the importance of adapting instructional approaches to align with these differences, thereby fostering more effective learning experiences. This research aimed to evaluate the effectiveness of differentiated instruction tailored to students’ learning styles in improving learning outcomes among third-grade students at SD Negeri Pao-Pao, Gowa Regency. Employing a quantitative approach with a one-group pretest–posttest experimental design, the study involved 29 students. Instruments included written tests and a VARK-based learning style questionnaire, and data were analyzed using normality and homogeneity tests, followed by one-way ANOVA to examine differences in learning outcomes across the three learning style groups. The results showed that while statistical differences among visual, auditory, and kinesthetic learners were not significant, each group exhibited notable gains in posttest scores. Visual learners benefited most from the use of diagrams and multimedia, auditory learners from discussion-based learning, and kinesthetic learners from hands-on activities. These findings indicate that differentiated instruction—when responsive to learning preferences—can significantly enhance students’ engagement and overall academic achievement. The study contributes to the growing body of evidence supporting inclusive and adaptive pedagogy in Indonesian elementary education and provides practical recommendations for teachers to incorporate multimodal strategies in lesson planning while encouraging policymakers to promote professional development programs focused on differentiated instruction as a pathway to improving learning equity and quality.